2009
DOI: 10.1099/jmm.0.003780-0
|View full text |Cite
|
Sign up to set email alerts
|

Vibrio cholerae O1 clinical strains isolated in 1992 in Kolkata with progenitor traits of the 2004 Mozambique variant

Abstract: Retrospective analysis led to the detection of two Vibrio cholerae variant O1 strains (VC51 and VC53), which were isolated in 1992 in Kolkata from clinical cases, with identical traits to 2004 Mozambique variant O1 strains. The Mozambique O1 strains that caused a huge outbreak in 2004 have been shown to have phenotypic traits of both classical and El Tor biotypes, and thereby have been reported as variant. Our study demonstrated that two O1 strains isolated in Kolkata during 1992 were of the El Tor background … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
23
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 23 publications
3
23
1
Order By: Relevance
“…Since the Mozambique hybrid strain evolved in 2004, and the Kolkata hybrid strains were isolates of 1992, the latter strains may thus be the progenitors of the former strain. Recently Chatterjee et al (2009) have also provided evidence in favour of this conclusion by using ribotyping and other molecular methods. The small chromosomal arrangement of the classical CTX prophage is identical in the Mozambique and Kolkata hybrid El Tor strains (Faruque et al, 2007;Das et al, 2007), which also supports their ancestry.…”
Section: Resultsmentioning
confidence: 96%
“…Since the Mozambique hybrid strain evolved in 2004, and the Kolkata hybrid strains were isolates of 1992, the latter strains may thus be the progenitors of the former strain. Recently Chatterjee et al (2009) have also provided evidence in favour of this conclusion by using ribotyping and other molecular methods. The small chromosomal arrangement of the classical CTX prophage is identical in the Mozambique and Kolkata hybrid El Tor strains (Faruque et al, 2007;Das et al, 2007), which also supports their ancestry.…”
Section: Resultsmentioning
confidence: 96%
“…Genetic analysis of the tcpA gene also is routinely conducted to verify the biotype background of V. cholerae isolates (4,11,34,45) and was used in this study. The tcpA gene in all clinical variants in this study was sequenced and confirmed to be of the El Tor biotype, with three mutations (Table 5).…”
Section: Discussionmentioning
confidence: 99%
“…Although evidence has been presented demonstrating that the El Tor biotype has globally displaced the classical biotype (19,42), the emergence of El Tor variants has warranted the use of standard genotypic and phenotypic assays to determine the biotype background of new isolates. Standard phenotypic assays, including polymyxin B resistance, hemolysis assays, phage sensitivities, and the Voges-Proskauer tests, are frequently employed in some combination (4,11,45). Genetic markers, such as the ctxB gene, have been used to distinguish the cholera toxin between classical and El Tor biotypes (11,33,35) to classify isolates as El Tor variants.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, 2 V. cholerae strains, VC51 and VC53, isolated in 1992 in Kolkata were identified as progenitor of 2004 Mozambique variants (Chatterjee et al, 2009). Subsequent analysis of archived strains revealed complete replacement of ctxB El by the ctxB cl in Kolkata strains since 1995 .…”
Section: Introductionmentioning
confidence: 97%